Engaged, Exhausted or Indifferent? Study Environment Factors and Doctoral Students’ Well-being - Žiedelis, Arūnas (Psichologija, 2022)
Creating decent conditions for doctoral students is a challenge that higher education institutions do not always manage to cope with. This tendency is also indirectly seen in the indicators of the well-being of doctoral students. The purpose of this study was to distinguish different well-being groups of doctoral students and to identify predictors of belonging to them. 633 doctoral students from various fields of science participated in the study, and were asked to answer questions about their study engagement, exhaustion, and the main study environment characteristics (demands and resources). The applied cluster analysis revealed that according to study engagement and burnout, four groups of doctoral students’ well-being can be distinguished, i.e., successful, exhausted, burned-out and indifferent doctoral students. Regression analysis made it possible to distinguish four study environmental characteristics that differentiate different groups of doctoral students’ well-being. Fewer opportunities for development, lack of support from the dissertation supervisor, higher study load, and more frequent encounters with conflicting expectations were associated with a lower probability of belonging to the group of doctoral students of the highest well-being. The results show that the antecedents for the well-being of doctoral students should be sought in the institutional environment, which facilitates or complicates the implementation of the tasks. The article also discusses suggestions based on the research results to improve the process of training doctoral students.